Colorectal Cancer Cells Adhere to Traumatized Peritoneal Tissue in Clusters, An Experimental Study. (4th July 2018) - Falk, Peter; Jonsson, Andreas; Swartling, Torbjörn; Ivarsson, Marie-Lois
ABSTRACT: Purpose/Aim: Colorectal malignity is one of the most common forms of cancer. The finding of free intraperitoneal colorectal cancer cells during surgery has been shown to be associated with poor outcome. The aim of this study was to develop an experimental model designed to investigate adhesion of colorectal cancer cells to the peritoneal surface. Materials and methods: Two human experimental models were developed, the first using cultured mesothelial cells and the second consisting of an ex vivo model of peritoneal tissue. Both models were subjected to standardized trauma, following which labeled colorectal cancer cells (Colo205) were introduced. Adhesion of tumor cells was monitored using microscopy and detection of fluorochromes. Results: The mesothelial cell layers and peritoneal membranes remained viable in culture medium for several weeks. In our experimental model, the tumor cells added were seen to adhere to the edges of the traumatized area in cluster formations. Conclusions: The use of human peritoneal tissue in an ex vivo model would appear to be a potentially useful tool for the study of interaction between human peritoneal membrane and free tumor cells. Experimental surgical trauma increases the ability of tumor cells to adhere to the peritoneal membrane. This ex vivo model should be useful in future studies on biological interactions between peritoneum and tumor cells in the search for novel forms of peritoneal cancer therapy.